2023
DOI: 10.1109/tsmc.2022.3229213
|View full text |Cite
|
Sign up to set email alerts
|

MARL Sim2real Transfer: Merging Physical Reality With Digital Virtuality in Metaverse

Abstract: Metaverse is an artificial virtual world mapped from and interacting with the real world. In metaverse, digital entities coexist with their physical counterparts. Powered by deep learning, metaverse is inevitably becoming more intelligent in the interactions between reality and virtuality. However, it is confronted with a nontrivial problem known as sim2real transfer when deep learning techniques try to bridge the reality gap between the physical world and simulations. In this article, we use multiagent deep r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
(69 reference statements)
1
0
0
Order By: Relevance
“…In particular, various computational experiments considering human and social factors were conducted, evaluated, and shared with the real VCS system to improve its efficiency and robustness. Similar studies can be found in transportation systems [38], healthcare [39], education [40], and image encryption [41].…”
Section: Parallel Intelligent Systemssupporting
confidence: 68%
“…In particular, various computational experiments considering human and social factors were conducted, evaluated, and shared with the real VCS system to improve its efficiency and robustness. Similar studies can be found in transportation systems [38], healthcare [39], education [40], and image encryption [41].…”
Section: Parallel Intelligent Systemssupporting
confidence: 68%
“…They defined the spectrum resource allocation problem as a discrete Markov decision process, and developed a quantum-inspired reinforcement learning mechanism to optimize the distributed vehicle selection policy. Shi et al [32] employed multi-agent reinforcement learning scheme to model the collective intelligence in digital entity, aiming to enhance the immersive environment in Metaverse. They implemented a deep deterministic policy gradient for the domain randomization, which could assist a perception-control modularization for the improvement of generalization performance in multiple unmanned aerial vehicle systems.…”
Section: Metaverse Applicationsmentioning
confidence: 99%
“…Falchuk et al analyzes privacy in the social metaverse. The article raises concerns about users' privacy in shared virtual environments and highlights the im-portance of addressing privacy challenges to ensure a secure experience in the metaverse (Shi, G, 2023).…”
Section: B Security and Privacy In The Metaversementioning
confidence: 99%